Synergistic effects and kinetics analysis of biochar with semi-coke during CO2 co-gasification. (15th January 2020) - Wang, Qi; Wang, Enlu; Li, Kai; Husnain, Naveed; Li, Deli
Abstract: It is well-known that there is an interaction between biomass and coal in co-gasification process. In this paper, gasification of semi-coke (SC) and soybean straw char (SS) and their blends were carried out using non-isothermal thermogravimetric method. Interaction between SS and SC during co-gasification was investigated and synergy factors were calculated at different conversion stage. In order to explore whether the physical and chemical structure features have an effect on interaction, surface area analyzer, XRF and Raman spectrometer were adopted to determine the porous properties, ordering degree and ash composition for blends. The results show that the changes of porous properties and ordering degree for blends follow a linear law. The correlation expressions linking char characteristics to char reactivities indicate that the degree of graphitization is the main reason influencing the gasification reactivity. The interaction exhibits a negative synergetic effect at low conversion stage and a positive synergetic effect at high conversion stage. In addition, there are significant synergistic effects in the co-gasification of 75%SC/25%SS. Similar conclusions about synergetic effect are also observed from the kinetics data calculated by three kinetic models. Highlights: The biochar reactivities significantly greater than that of semi-coke. The reactivities of biochar and semi-coke correlate well with their properties. The increasing proportion of biochar weakens synergies during co-gasification. Synergies on gasification of char vary with biochar/semi-coke mass ratio. SF < 1 at low conversion stage and SF ＞1 at high conversion stage for co-gasification.